Educação, história e cultura nos cadernos culturais organizados pelo Departamento de Cultura, em Francisco Beltrão- Paraná (2001 a 2012) com base na colonização do município - Guadanhin, Jaciliane Casanova (2023)
The present study is developed within the scope of the Postgraduate Program in Education - Master's Degree, at the Francisco Beltrão Campus, Paraná, at the State University of Western Paraná (Unioeste). The program's area of concentration is Education, and the Research Line is called Culture, Educational Processes and Teacher Training. The general objective of the research is to understand the educational, historical and cultural aspects in the cultural notebooks that were produced organized by the Department of Culture in the municipality of Francisco Beltrão, in the period from 2001 to 2012 in relation to the colonization of the city. This general objective unfolds into two specific objectives that will be dealt with in different chapters, the objective of the first chapter will be: to contextualize the Department of Culture, Municipal Memorial and the Francisco Beltrão Memory Project. In the second chapter, the objective is to: identify educational, historical and cultural aspects of the municipality of Francisco Beltrão, considering the colonization perspective, in the cultural notebooks produced in the period from 2001 to 2012. The problem that drives the research is: Do the elaboration of 16 cultural notebooks covering different themes, correspond to the events of the colonization of the municipality of Francisco Beltrão? In this context, the research seeks to understand whether in this dynamic there are aspects of education, history and culture of the region, in a way that is described, being able to provide the reader with an interpretation of the facts. To this end, the following hypothesis was developed: the cultural notebooks integrated research with diverse content, with reports, photographs, writings and other artifacts that contributed to the education, history and culture of the municipality of Francisco Beltrão. In this way, this production permeates current times through research, demonstrating to the reader perspectives on education, history and local culture. To carry out the research, the methodology used is bibliographic and documentary. To analyze the collected material, the research has the support of experts using educational, historical and cultural references. The results of the research are the presence of education, history and culture in the cultural notebooks, giving the reader the opportunity to know and understand the history of the colonization of the municipality of Francisco Beltrão, Paraná in the face of the different events that impacted the process of occupation of land and by ways in which they related.